COMPARISON OF VAC DRESSING AND SOFRA DRESSING IN DIABETIC FOOT WOUND IN TERTIARY CARE HOSPITAL OF SOUTH PUNJAB - HASSAN , G; SABIR , M; YASEEN , G; ALAM , I; FAREED, N; ASIM, I (Biological and Clinical Sciences Research Journal, 2024)
Diabetic foot ulcers (DFUs) are a significant complication of diabetes, contributing to high morbidity and healthcare costs. Vacuum-assisted closure (VAC) therapy is a promising intervention for DFU management, but its adoption in Pakistan is limited. Objective: This study aimed to compare the effectiveness of VAC therapy and conventional Sofra dressing in managing DFUs in a tertiary care hospital. Methods: A prospective comparative study was conducted among 120 patients with Wagner grade 2 or 3 DFUs. Participants were randomly assigned to two groups: Group A (VAC therapy) and Group B (Sofra dressing). Data on wound surface area reduction, granulation tissue formation, and demographic variables were collected over four weeks. Statistical analysis was performed using SPSS version 26, with a p-value of <0.05 considered significant. Results: VAC therapy demonstrated superior outcomes compared to Sofra dressing. The mean wound surface area reduction was 45% in Group A and 25% in Group B. Granulation tissue formation occurred significantly faster in the VAC group (14.90 ± 9.11 days) compared to the Sofra group (29 ± 5.81 days) (p < 0.05). No significant gender differences were observed, but younger patients (<55 years) experienced slightly faster healing rates in both groups. Conclusion: VAC therapy is more effective than conventional Sofra dressing in reducing wound size and promoting faster granulation tissue formation in diabetic foot ulcers. These findings support the adoption of VAC therapy as a standard intervention for DFU management in Pakistan, despite resource limitations. Policy-level support and training are essential for its widespread implementation..